Effects of cattle husbandry on abundance and activity of methanogenic archaea in upland soils - Radl, Viviane; Gattinger, Andreas; Chronáková, Alica; Nemcová, Anna; Cuhel, Jiri; Simek, Miloslav; Munch, Jean Charles; Schloter, Michael; Elhottová, Dana (The ISME journal, 2007)
In the present study, we tested the hypothesis that animal treading associated with a high input of organic matter would favour methanogenesis in soils used as overwintering pasture. Hence, methane emissions and methanogen populations were examined at sections with different degree of cattle impact in a Farm in South Bohemia, Czech Republic. In spring, methane emission positively corresponded to the gradient of animal impact. Applying phospholipid etherlipid analysis, the highest archaeal biomass was found in section severe impact (SI), followed by moderate impact (MI) and no impact. The same trend was observed for the methanogens as showed by real-time quantitative PCR analyses of methyl coenzyme M reductase (mcrA) genes. The detection of monounsaturated isoprenoid side chain hydrocarbons (i20:1) indicated the presence of acetoclastic methanogens in the cattle-impacted sites. This result was corroborated by the phylogenetic analysis of mcrA gene sequences obtained from section SI, which showed that 33% of the analysed clones belonged to the genus Methanosarcina. The majority of the sequenced clones (41%) showed close affiliations with uncultured rumen archaeons. This leads to the assumption that a substantial part of the methanogenic community in plot SI derived from the grazing cattle itself. Compared to the spring sampling, in autumn, a significant reduction in archaeal biomass and number of copies of mcrA genes was observed mainly for section MI. It can be concluded that after 5 months without cattle impact, the severely impact section maintained its methane production potential, whereas the methane production potential under moderate impact returned to background values.
Keywords: Euryarchaeota; Phylogeny; chov zvířat; Methane; Soil Microbiology; zvířata; biomasa; genetická variace; Genetic Variation; roční období; archeální geny; Cattle; fylogeneze; Seasons; půdní mikrobiologie; Czech Republic; skot; Animal Husbandry; Animals; Biomass; Česká republika; Genes, Archaeal; methan